Analisis dan Perbaikan Kondisi Ketenagakerjaan Unit V (lima) Bagian Packaging dengan Metode Workload Analysis dan Work Sampling dI PT.X - Leonardus Antonio; Prayonne Adi (Jurnal Titra, 2023)
PT. X is a manufacturing company that operates in the field of iodized salt production in Surabaya since 1978. With production capacity increasing every year, PT. X has established several production units to boost the company's work productivity. One of the production units that is referenced to boost work productivity dominantly is unit V (five). In unit V (five), there is one part that is important in helping into the final product distribution, namely the packaging section. The problem currently faced by the packaging section at unit V (five) is that there is an additional workforce that fluctuates at certain times without being balanced with considerations regarding job descriptions and the influence on ongoing work conditions or situations. Through an analysis of labor conditions using the workload analysis and work sampling methods, a high average workload percentage of 114.25% was obtained. In addition, through calculations and analysis of average standard time of 2,072 minutes/pc in the packaging section, the actual calculation of the optimal number of workers is 8 workers in order to create a conducive situation while working with a decreasing average workload percentage to 99.97%.